GENDER ANALYSIS IN CONTEMPORARY ISLAMIC DISCOURSE: INTEGRATION OF METODOLOGY APPROACH - Abdul Mufid (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2020)
Islamic law is a dynamic system because it is facilitated by several flexible methodologies. At present, there are various types of problems in Muslim societies which are the results or implications of the development of science and technology, and also the results of changes that occur in the structure of society. To deal with this reality, an integrated contemporary approach must be applied in the process of Islamic law research. Therefore, this article will try to outline an integrated approach to unite and integrate theories in Islamic law with social research methods. Basically, there are several models that have been introduced by several scholars relating to this integrated approach. All models have their strengths and weaknesses in this integrated approach. This article attempts to analyze the integration of Islamic legal theories with the methods of gender analysis and their relationship to the methods of social criticism. This is related to the problems in fiqh related to polygamy which are always debated until now and also to analyze the application of practices in the social and contemporary conditions of our society.